Correlations among Entrance Surface Air KERMA, KERMA-Area Product and Exposure Index in Chest Digital Radiography at Phramongkutklao Hospital - Kaewpookum, Pichan; Pongnapang, Napapong; Saengruang-Orn, Supakajee (เวชสารแพทย์ทหารบก, 2016)
Background: Currently, Department of Radiology, Phramongkutklao Hospital is using digital radiological techniques instead of film-screen technique. Digital radiological techniques offer the higher image quality and better data managing compared with film. In practice, however, higher radiation doses are correspondingly possible because of a broader dynamic range of digital image receptors than film-screen system. According to protection against ionizing radiation exposure, as low as reasonably achievable (ALARA) concept, patients undergoing medical x-ray should be treated under diagnostic reference level (DRL) of radiation exposed. The local diagnostic reference level such as entrance surface air kerma, kerma area product and exposure index can be established for Phramongkutklao Hospital as one of tool for patients care management. Objective: To determine the correlation among entrance surface air kerma, kerma-area product, and exposure index of patient who underwent chest digital radiography prior to establish a dose referent level in Phramongkutklao hospital. Methodology: A retrospective study of 215 chest digital radiographs data tags from April 2012 to June 2012 at Phramongkutklao hospital and calibrating of a built-in Kerma Area Product (KAP) meter were done to determine the correlation among entrance surface air kerma, kerma-area product, and exposure index. Result: Mean entrance surface air kerma using KAP- meter was 0.1196 mGy, mean kerma-area product was 0.12 Gycm2, and mean exposure index was 1209 mbels. There was a strong correlation between entrance surface air kerma and kerma-area product (r = 0.983).Correlation between exposure index and entrance surface air kerma was not significant (r = -0.2). Correlation between exposure index and kerma area product was not significant (r = -0.101). Conclusion: KAP-meter is a reliable dose monitoring tool if calibrated properly. In case of insufficient of KAP-meter, Entrance surface air kerma can be calculated by x-ray output in the range of clinical beam quality. Exposure index has shown a poor correlation to either kerma area product or entrance surface air kerma due to the improper collimation. The local diagnostic reference level (DRL) of each digital imaging procedure in Phramongkutklao hospital should be established by radiologist and medical physicist. สหสัมพันธ์ของปริมาณรังสีที่ผิวหนัง ผลคูณเคอร์มา-แอเรีย และดัชนีเอกโพเชอร์ ในการตรวจเอกซเรย์ปอดระบบดิจิตอล ณ โรงพยาบาลพระมงกุฎเกล้า ความเป็นมา : ปัจจุบันโรงพยาบาลพระมงกุฎเกล้า ได้ใช้การถ่ายเอกซเรย์ระบบดิจิตอลแทนการใช้ฟิล์ม ระบบดิจิตอลให้ภาพที่มีคุณภาพสูงและสามารถบริหารจัดการได้ง่ายกว่าฟิล์มอย่างไรก็ตามในทางปฏิบัติคนไข้อาจได้รับปริมาณรังสีสูงเกินกว่าความจำเป็น เนื่องจากในระบบดิจิตอลมีค่า dynamic range ที่กว้างแม้เจ้าหน้าที่ให้ปริมาณรังสีสูงภาพก็จะไม่ดำเกินไป (õver exposure) จากหลักการป้องกันทางรังสีผู้ป่วยที่ได้รับรังสีทางการแพทย์ควรมีระดับไม่เกินระดับรังสีอ้างอิงของการตรวจทางรังสีแต่ละประเภท (diagnostic reference level) ค่าปริมาณรังสีที่ผิวหนัง ผลคูณเคอร์มา-แอเรีย และดัชนีเอกโพ-เชอร์ เป็นค่าที่สามารถใช้เป็นระดับรังสีอ้างอิงของโรงพยาบาลพระมงกุฎเกล้าได้ วัตถุประสงค์ : เพื่อหาค่าสหสัมพันธ์ของปริมาณรังสีที่ผิวหนัง ผลคูณเคอร์มา-แอเรีย และดัชนีเอกโพเชอร์ ในการตรวจเอกซเรย์ปอดระบบดิจิตอล ณ โรงพยาบาลพระมงกุฎเกล้า สำหรับสร้างระดับรังสีอ้างอิงต่อไป วิธีการศึกษา : ใช้วิธีการศึกษาย้อนหลังข้อมูลประกอบภาพเอกซเรย์ปอดระบบดิจิตอลสองร้อยสิบห้ารายของผู้ที่มาตรวจในช่วงเดือนเมษายน - เดือนมิถุนายน พ.ศ. 2555 ณ โรงพยาบาลพระมงกุฎเกล้าร่วมกับการสอบเทียบแคพมิเตอร์ (KAP - meter) เพื่อคำนวณหาค่าปริมาณรังสีที่ผิวหนัง ผลคูณเคอร์มา -แอเรีย และดัชนีเอกโพเชอร์ ผลการศึกษา : ค่าเฉลี่ยปริมาณรังสีที่ผิวหนังคือ 0.1196 มิลลิเกรย์ ค่าผลคูณเคอร์มา - แอเรีย คือ 0.12 เกรย์ตารางเซนติเมตร และดัชนีเอกโพเชอร์มีค่า 1,209 mbels. ค่าสหสัมพันธ์ระหว่างปริมาณรังสีที่ผิวหนังและผลคูณเคอร์มา แอเรียค่อนข้างสูง (r = 0.983) ในขณะที่ค่าสหสัมพันธ์ระหว่างดัชนีเอกโพเชอร์และค่าอื่น ๆ ค่อนข้างต่ำ (r ≤ -0.2) สรุป : แคพมิเตอร์เป็นเครื่องมือที่น่าเชื่อถือในการวัดปริมาณรังสีที่ผู้ป่วยได้รับหากมีการสอบเทียบเครื่องมือที่เหมาะสมในกรณีที่หน่วยงานใดไม่มีแคพมิเตอร์สามารถใช้ค่าปริมาณรังสีที่ผิวหนังซึ่งได้จากการคำนวณค่าปริมาณรังสีที่ให้แก่ผู้ป่วยเป็นตัวกำหนดระดับรังสีอ้างอิงได้ ค่าดัชนีเอกโพเชอร์ที่ไม่มีสหสัมพันธ์กับค่าอื่น ๆ เนื่องจากการเปิดลำรังสีที่ไม่เหมาะสม ระดับรังสีอ้างอิงสำหรับการตรวจทางรังสีทุกประเภทในโรงพยาบาลพระมงกุฏเกล้าควรกำหนดขึ้นโดยรังสีแพทย์และนักฟิสิกส์การแพทย์